The Impact of Social Media Marketing Activity of Instagram towards Brand Experience, Consumer-Based Brand Equity, and Re-Subscribe Intention. A Case Study of Netflix Indonesia (Journal of Business and Management, 2022)
Netflix is a US-based pioneer of video-on-demand (VOD) service. It provides a variety of movies and TV series, and even produces its own original shows. As the VOD industry is growing in Indonesia, many newcomers are entering the market. Hence, Netflix's position is threatened. An increasing price of subscription also gives rise to what Netflix faces challenges, which subsequently create tremendous loss of subscribers in Netflix US. The same occurrence might possibly happen in Indonesia. Netflix Indonesia is heavily carrying out their marketing strategy online through social media. This study intends to examine how social media marketing activity could enhance brand experience, consumer-based brand equity, and re-subscribe intention. This research utilizes a quantitative survey in which the primary data is gathered from 270 respondents who have followed Netflix Indonesia Instagram and have been subscribing to Netflix for at least 3 months. The result indicates that social media marketing significantly influences brand experience, consumer-based brand equity, and re-subscribe intention with brand experience as a partial mediator of SMMA in influencing CBBE. It is expected that academic and managerial suggestions obtained by the result could enhance marketer comprehension on how SMMA could improve brand experience, consumer-based brand equity, and re-subscribe intention.Keywords: Netflix Indonesia; Video-on-Demand (VOD), Social Media Marketing (SMM), Brand Experience, Consumer-Based Brand Equity (CBBE), and Re-subscribe Intention